The repetitive transcranial magnetic stimulation in Alzheimer's disease patients with behavioral and psychological symptoms of dementia: a case report - Zhen Yang; Ying Zhou (BMC Psychiatry, 2023)
Abstract Background Repetitive transcranial magnetic stimulation is a noninvasive intervention, can significantly reduce behavioral and psychological symptoms and cognitive impairment in AD patients. Only few cases have been reported the adverse reactions after the treatment. This report described the different adverse reactions after repetitive transcranial magnetic stimulation with different parameters. Patient presentation This article reports a patient with dementia complicated with mental behavior disorder who was treated with repetitive transcranial magnetic stimulation (rTMS) in spite of poor drug response. First, 1 Hz rTMS was initiated. After 1 month, the patient showed improved symptoms of mental behavior, decreased cognitive function and prolonged sleep duration. After switched to 10 Hz rTMS, the patient’s cognitive function and mental behavior abnormalities improved, and the sleep time returned to normal. However, epilepsy occurred after one session and was changed to 0.8 Hz rTMS treatment. The patient’s symptoms improved and did not have seizure. Conclusion Repetitive transcranial magnetic stimulation has a positive effect on cognitive function and Behavioral And Psychological Symptoms Of Dementia, and adverse reactions are inevitable. Playing personalized treatment according to the patients can reduce occurrence of adverse reactions.